Regulation of the autophagy-marker Sequestosome 1 in periodontal cells and tissues by biomechanical loading - Memmert, S.; Nogueira, A. V. B.; Damanaki, A.; Nokhbehsaim, M.; Rath-Deschner, B.; Goetz, W.; Gölz, Lina; Cirelli, J. A.; Till, A.; Jaeger, A.; Deschner, J. (Journal of Orofacial Orthopedics / Fortschritte der Kieferorthopädie, 2019)
Purpose Orthodontic treatment is based on the principle of force application to teeth and subsequently to the surrounding tissues and periodontal cells. Sequestosome 1 (SQSTM1) is a well-known marker for autophagy, which is an important cellular mechanism of adaptation to stress. The aim of this study was to analyze whether biomechanical loading conditions regulate SQSTM1 in periodontal cells and tissues, thereby providing further information on the role of autophagy in orthodontic tooth movement. Methods Periodontal ligament (PDL) fibroblasts were exposed to cyclic tensile strain of low magnitude (3%, CTSL), and the regulation of autophagy-associated targets was determined with an array-based approach. SQSTM1 was selected for further biomechanical loading experiments with dynamic and static tensile strain and assessed via real-time polymerase chain reaction (RT-PCR) and immunoblotting. Signaling pathways involved in SQSTM1 activation were analyzed by using specific inhibitors, including an autophagy inhibitor. Finally, SQSTM1 expression was analyzed in gingival biopsies and histological sections of rats in presence and absence of orthodontic forces. Results Multiple autophagy-associated targets were regulated by CTSL in PDL fibroblasts. All biomechanical loading conditions tested increased the SQSTM1 expression significantly. Stimulatory effects of CTSL on SQSTM1 expression were diminished by inhibition of the c-Jun N-terminal kinase (JNK) pathway and of autophagy. Increased SQSTM1 levels after CTSL were confirmed by immunoblotting. Orthodontic force application also led to significantly elevated SQTSM1 levels in the gingiva and PDL of treated animals as compared to control. Conclusions Our in vitro and in vivo findings provide evidence of a role of SQSTM1 and thereby autophagy in orthodontic tooth movement.
CRIS-Team WoS Importer:2019-10-25